INOVASI APLIKASI MAGELANG CERDAS BERBASIS SMART CITY DI KOTA MAGELANG - Brigitta Sekar Febrianti; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Diskominsta of Magelang City launched a Smart City-based innovation in Magelang City in the form of Magelang Cerdas application. Magelang Cerdas is an android-based application that is expected to facilitate the community in obtaining public information/services in Magelang City. This study aims to analyze one of the success criteria of innovation according to Arundel et al (in Milasari and Oktariyanda, 2022: 1043), namely Governance and Innovation and analyze the obstacles in the implementation of Magelang Cerdas application innovation. The results showed that the criteria of governance and innovation in the innovation of Magelang Cerdas application are running well but not yet optimal. It is proven by the role of Diskominsta of Magelang City and the establishment of Magelang Cerdas app innovation. There are obstacles in the innovation of Magelang Cerdas application, including: (a) socialization conducted by the Department of Communication Information and Statistics of Magelang City related to Magelang Cerdas application has not run optimally ((b) Magelang Cerdas application has not been based on IOS (c) there is a digital divide in the community of Magelang City